Consumer Behavior In Digital Banking Among Gen Z In Surabaya - Fiana Dwi Wiyanti; Zumrotul Fitriyah; Wilma Cordelia Izaak (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The development of technology is an essential part of various aspects of life, including the economy. This also encouraged the transition from using physical to digital payment, which has positively impacted the banking industry. BLU by BCA Digital is a digital bank to answer necessity of digital era. That makes ease of use perception a crucial aspect, with contribution from BLU by BCA Digital’s brand image as part of the BCA Group. This research examines the contribution of perceived ease of use on the intention to use through brand image as an intervening variable of BLU by BCA Digital in Surabaya. By using quantitative and statistical data analysis descriptive with SEM-PLS, this research is limited to the research population, which is M-BCA customers in Surabaya. The sample in this study is 100 M-BCA customers aged 17-27 years who are part of Generation Z and familiar with BLU by BCA Digital. The results show that Perceived Ease Of Use (X) and Brand Image (Z) have a contribution to Intention To Use (Y), Perceived Ease Of Use (X) has a contribution to Brand Image (Z), and Brand Image (Z) able to strengthen the contribution in the midst of Perceived Ease Of Use (X) and Intention To Use (Y) BLU by BCA Digital in Surabaya as an indirect effect.